SUATU TINJAUAN MONITORING DAN EVALUASI (MONEV) KETERBUKAAN INFORMASI PUBLIK PERANGKAT DAERAH PROVINSI BANTEN - Toni Anwar Mahmud (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2023)
Abstract The implementation of public information disclosure in Banten Province has been running for 11 years. Compliance with the implementation of information disclosure is supervised by the Banten Province Information Commission which carries out monitoring and evaluation (monev) of regional apparatus in the Banten Provincial Government every year. This research method uses a descriptive method with a qualitative approach. Data collection is done through interviews along with scientific findings. Data comes from interviews. The results of the research show that the monitoring and evaluation carried out in 2022 resulted in only 81.83% of regional apparatus developing their website and the aspect of announcing public information, only 77.5% of regional apparatus. In terms of qualifications, out of 32 regional apparatuses, there are 13 regional apparatuses with informative qualifications, 1 regional apparatus with qualifications towards informative, 17 regional apparatuses with moderately informative qualifications and 1 regional apparatus with less informative qualifications. Monev every year which is carried out by the Information Commission has not had an impact on the compliance of regional apparatus in announcing and serving public information. There needs to be innovation from the Information Commission to give a deterrent effect to regional apparatuses who are ignorant of the obligation to announce and serve public information. With regard to the frequent changes and transfer of employees due to rotation, employee mutation. The Banten Provincial Information Commission can work together with the Human Resources Development Agency and the Banten Province Personnel Agency to provide education and training to every state civil apparatus in the Banten Provincial Government so that each apparatus has an understanding of their obligations to implement the UU KIP.